2016
DOI: 10.1002/jssc.201600083
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of major constituents from Xue Fu Zhu Yu Decoction using ultra high performance liquid chromatography with hybrid ion trap time‐of‐flight mass spectrometry

Abstract: Xue Fu Zhu Yu Decoction, a famous formula that has been used for treating many blood stasis-caused diseases for many centuries, comprises 11 kinds of traditional Chinese medicines. A convenient, efficient, and rapid analytical method was developed to simultaneously determine the major compounds in this decoction. An ultra-high performance liquid chromatography with hybrid ion trap time-of-flight mass spectrometry method was used to rapidly separate and detect the major constituents of the decoction. Using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Xue-Fu-Zhu-Yu decoction (XFZYD) is a famous traditional Chinese medicine formula that has been used to manage with cardiovascular disorders for several centuries [10]. The study of Lee et al [11] suggested that XFZYD increased the potential of recombinant tissue plasminogen activator (tPA) as a neuroprotection agent against rat brain ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Xue-Fu-Zhu-Yu decoction (XFZYD) is a famous traditional Chinese medicine formula that has been used to manage with cardiovascular disorders for several centuries [10]. The study of Lee et al [11] suggested that XFZYD increased the potential of recombinant tissue plasminogen activator (tPA) as a neuroprotection agent against rat brain ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…M17 showed a [M + H] + ion at m/z 255.0557 and a [M−H] − ion at m/z 253.0498, and the formula was calculated as C 15 H 10 O 4 , which was 2 Da (2H) less than the protonated ion of liquiritigenin. The produced major fragment ions at m/z 209.1142 [M–H–CO 2 ] − , 135.0315 [M–H–C 8 H 6 O] – , and 117.1369 [M–H–C 7 H 4 O 3 ] – were found in negative mode . M17 was tentatively identified as the dehydrogenation version of liquiritigenin.…”
Section: Resultsmentioning
confidence: 99%
“…This regulation contains several proteins which consist of certain pathways (Figure 2A ). The CIDs of the 34 identified compounds of XFZYD were submitted into BATMAN-TCM [ 37 , 41 ]. Interestingly, the results showed that the main druggable target-LTP pathway was anchored by KEGG enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to investigate whether XFZYD provided a synaptic regulation to improve cognitive function after TBI. The PubChem Compound IDs (CIDs) of the key compounds of XFZYD were submitted into BATMAN-TCM to predict the druggable targets related to synaptic function [ 37 , 41 ]. We further verified this prediction by molecular biological methods (Immunohistochemical, RT-PCR and western blot analyses).…”
Section: Introductionmentioning
confidence: 99%